Variability in chert raw material procurement and use during the Upper Paleolithic and Early Neolithic of the southern Levant: A regional perspective from the Greater Petra area. (February 2020) - Parow-Souchon, Hannah; Purschwitz, Christoph
Highlights: Chert acquisition is a function of quality/intended use and cost-distance to the source. Significant changes occur in between Upper Paleolithic and Neolithic chert acquisition. For complex methods high quality cherts are procured at extended cost. Past human groups exploit the same raw material sources differently. Abstract: In SW Asia, chert procurement studies have received increasing attention in the last two decades. However, studies on chert availability and procurement are often focused on single sites or inventories and characterize different groups of cherts for each site, complicating cross-site comparisons. Our paper aims to show the potential of lithic studies if similar standards in raw material description and analysis of availability are applied in a cross-project and diachronic study. We analyzed more than 25, 000 lithic artefacts from nine Upper Paleolithic to Early Neolithic sites in the southern Levantine Greater Petra Region. Parameters of study include the identification of flint raw material groups (FRMG), the analysis of cortex or remains of natural surfaces, the geological availability of FRMGs within the Greater Petra Region, and a minimal distance analysis (MDA) of chert raw materials for the sites based on least-cost-models. Two chert raw material surveys, conducted in 2012 and 2015, show that primary source areas of most FRMG in the Greater Petra Region are restricted to two geological formations and are a suitable tool for predictive source modelling. The spectrum of used FRMG among the sites and periods is very variable, with the tendency of a wider spectrum in early Neolithic, and a more restricted one in Upper Paleolithic sites. Upper Paleolithic inventories show either a very targeted and direct procurement of lithic material, or an embedded one - resulting in greater raw material diversity. Pre-Pottery Neolithic B (PPNB) lithic economies are characterized by increasing complexity and craft specialization. Specialized (surplus) production of standardized bidirectional blades co-exist with a generalized household production (non-standardized and assumed to be primarily self-sufficient). While the generalized household production shows very opportunistic modes of chert procurement (often gathered from nearby wadi fills), the raw material procurement for specialized production is characterized by a clear preference for high-quality cherts from primary sources. Generally, only one or two chert types are processed per workshop. We suggest that different socio-economic settings contribute to the variabilities observed and use a multivariate statistical method (Canonical Correspondence Analysis) to test selected binary covariables (chronological and cultural affiliation and PPNB blade technology) for significance. All tested covariables show significant differences in raw material procurement behavior. A general trend is observable towards increasing complexity in procurement processes mirroring the more complex ways of life in the Early Neolithic Period. In general, lithic economy in the Greater Petra Region shows a diachronic consistency of high investment if high quality cherts are needed, and a low investment if no special demands are placed on the material.